2019
DOI: 10.1186/s41983-019-0128-1
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-based study of post-stroke aphasia: frequency, risk factors, and topographic representation

Abstract: Background and objective: The crude prevalence rate of stroke in Qena, Egypt, is high (922/100,000). For the first time, we estimate the frequency of aphasia following the first-ever ischemic stroke and its relationship to the site of lesion in Arabic-speaking countries. Methods: The study was conducted on 180 acute or subacute ischemic stroke patients. Aphasia was diagnosed with the short form of the Boston Diagnostic Aphasia Examination after establishment of the cases (at least 10 days of stroke onset). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
2
12
1
1
Order By: Relevance
“…16 Up to 38% of stroke patients suffer from aphasia. 17 Post-stroke aphasia affects patients’ ability to express or understand language and disrupts their socialisation and work. Patients most often receive speech and language rehabilitation, neuromodulation, and pharmacological therapy (eg, bromocriptine, piracetam, and donepezil).…”
Section: Evidence Based Acupuncture Therapies Are Underusedmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Up to 38% of stroke patients suffer from aphasia. 17 Post-stroke aphasia affects patients’ ability to express or understand language and disrupts their socialisation and work. Patients most often receive speech and language rehabilitation, neuromodulation, and pharmacological therapy (eg, bromocriptine, piracetam, and donepezil).…”
Section: Evidence Based Acupuncture Therapies Are Underusedmentioning
confidence: 99%
“…The US National Aphasia Association estimated that 2 million people in the country and 250 000 people in the UK suffered from post-stroke aphasia in 2016 16. Up to 38% of stroke patients suffer from aphasia 17. Post-stroke aphasia affects patients’ ability to express or understand language and disrupts their socialisation and work.…”
Section: Evidence Based Acupuncture Therapies Are Underusedmentioning
confidence: 99%
“…Of the publications that were deemed relevant for the study, a few discussed rehabilitation and aphasia independent of stroke, and the emphasis is on multidisciplinary rehabilitation as opposed to just reporting on speech language pathology. This is because of the close association of stroke and aphasia (Khedr et al, 2020 ). By its nature, a stroke usually affects different areas including motor, communication, psychological and cognitive abilities, often impacting on participation and quality of life of the stroke survivor and their facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the most common cause of aphasia (Khedr et al, 2020 ). Approximately a third of stroke survivors experience aphasia (Van Oers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that about 21-38% of stroke patients develop aphasia. It has been reported that 20-40% of aphasias are of the global type, whereas the classic aphasia types, such as Broca's or Wernicke's aphasia, are found in a quarter of patients, and 10-15% of patients are unclassifiable according to traditional typologies during the acute stage of stroke (Khedr, et al .2020).…”
Section: Discussionmentioning
confidence: 99%